2014
DOI: 10.1080/02791072.2013.873157
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effects of Ritual Ayahuasca Use in the Treatment of Substance Dependence—Qualitative Results

Abstract: This qualitative empirical study explores the ritual use of ayahuasca in the treatment of addictions. Ayahuasca is an Amazonian psychedelic plant compound created from an admixture of the vine Banisteriopsis caapi and the bush Psychotria viridis. The study included interviews with 13 therapists who apply ayahuasca professionally in the treatment of addictions (four indigenous healers and nine Western mental health professionals with university degrees), two expert researchers, and 14 individuals who had underg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
110
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(119 citation statements)
references
References 22 publications
3
110
0
6
Order By: Relevance
“…In recent years, a renewed interest in psychedelic‐assisted therapy has generated mounting evidence linking therapeutic uses of psychedelics with improvements in problematic substance use , trauma and psychological well‐being . Ceremonial or ritualistic use of ayahuasca has been associated with reductions in substance use problems . Recently, the first randomised controlled trial on ayahuasca for treatment‐resistant depression was conducted in Brazil: findings demonstrated significant, rapid anti‐depressant effects following a single dose of ayahuasca compared to placebo .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a renewed interest in psychedelic‐assisted therapy has generated mounting evidence linking therapeutic uses of psychedelics with improvements in problematic substance use , trauma and psychological well‐being . Ceremonial or ritualistic use of ayahuasca has been associated with reductions in substance use problems . Recently, the first randomised controlled trial on ayahuasca for treatment‐resistant depression was conducted in Brazil: findings demonstrated significant, rapid anti‐depressant effects following a single dose of ayahuasca compared to placebo .…”
Section: Introductionmentioning
confidence: 99%
“…Our results are in agreement with pre‐clinical studies suggesting that the use of 5‐HT 2A agonists may be useful as therapeutic agents in the treatment of addiction (de Rios et al ., ; Thomas et al ., ; Johnson et al ., ; Loizaga‐Velder & Verres, ). Indeed, the findings are consistent with data showing that administration of 5‐HT 2A receptor agonists is negatively correlated with the development of addictive behavior in human populations (Gable, ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the findings are consistent with data showing that administration of 5‐HT 2A receptor agonists is negatively correlated with the development of addictive behavior in human populations (Gable, ). Furthermore, 5‐HT 2A receptor agonists have been reported to be therapeutically useful (Vargas‐Perez & Doblin, ) in producing long‐lasting relief from the negative symptoms associated with aversive motivational states such depression (de Lima Osório et al ., ) and addiction (Thomas et al ., ; Loizaga‐Velder & Verres, ).…”
Section: Discussionmentioning
confidence: 99%
“…25 Ayahuasca differs from the other substances covered in this review, inasmuch as it is a plantbased preparation of variable composition and strength, and typically used in ceremonial contexts, which makes it more difficult for researchers to isolate the factors that may contribute to therapeutic efficacy. 26,27 Posttraumatic stress disorder In a pilot randomized controlled trial investigating MDMA-assisted psychotherapy to treat chronic treatment-resistant PTSD in the United States, outcomes from 20 participants with a mean illness duration of 19 years showed that the experimental treatment may improve upon the best currently available pharmacotherapies and psychotherapies. 16 The clinical protocol in volved several weeks of preparatory and follow-up non-drugassisted psychotherapy, during which the members of the experimental group received two MDMA-assisted sessions.…”
Section: Addictionmentioning
confidence: 99%